2018
DOI: 10.1007/s11864-018-0566-5
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Immune System in Pancreatic Cancer

Abstract: Managing patients with metastatic pancreatic adenocarcinoma (mPDA) is a challenging proposition for any treating oncologist. Although the potency of first-line therapies has improved with the approvals of FOLFIRINOX and gemcitabine plus nab-paclitaxel, many patients are unable to derive significant benefit from later lines of therapy upon progression. Enrollment on clinical trials remains among the best options for patients with mPDA in all lines of therapy. At our institution, we routinely check for microsate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…PDAC, one of the most immunosuppressive tumors, educates resident and infiltrating immune cells towards this immunosuppressive state [ 59 ]. The immune cell compartment of the pancreatic TME mainly consists of tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs), and few activated cytotoxic effector T cells (CD8 + ) [ 60 ].…”
Section: Cafs Modulate the Immune Microenvironment And Crosstalk Wmentioning
confidence: 99%
“…PDAC, one of the most immunosuppressive tumors, educates resident and infiltrating immune cells towards this immunosuppressive state [ 59 ]. The immune cell compartment of the pancreatic TME mainly consists of tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs), and few activated cytotoxic effector T cells (CD8 + ) [ 60 ].…”
Section: Cafs Modulate the Immune Microenvironment And Crosstalk Wmentioning
confidence: 99%
“…Therefore, along with the recent development in sequencing technology, a personalized, molecular-targeted approach for PDAC is becoming an active area of research [9]. Several case studies showed a benefit of platinum-based chemotherapies or poly ADPribose polymerase (PARP) inhibitors for PDAC patients with BRCA1/2 abnormalities, and the NCCN guidelines suggest consideration of platinum-based regimen as a first-line therapy for advanced-stage pancreatic cancer patients with BRCA gene mutations [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The CSF-1 receptor (CSF-1R) inhibitor cabiralizumab was administered together with nivolumab in a phase I study for pretreated advanced pancreatic cancer patients. Four out of 31 patients had an ORR of 13% and of special interest all belong to the MSS subgroup [ 136 ]. Another phase I/II trial tested the combination of lacnotuzumab (anti-CSF-1 monoclonal antibody) with spartalizumab (PD-1 inhibitor).…”
Section: Chemotherapeutic Options In Msi Pancreatic Cancer Patientmentioning
confidence: 99%
“…Another phase I/II trial tested the combination of lacnotuzumab (anti-CSF-1 monoclonal antibody) with spartalizumab (PD-1 inhibitor). From the 13 patients with advanced pancreatic cancer, six patients had disease control with this combination and three of six had a disease control superior to 300 d [ 136 , 137 ].…”
Section: Chemotherapeutic Options In Msi Pancreatic Cancer Patientmentioning
confidence: 99%